2017
DOI: 10.1177/0193945917697218
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Motives to PA in South Asian Indian Immigrant Women

Abstract: The high prevalence of chronic illnesses in South Asian Indian immigrant women underscores the need for identifying factors that could influence their PA. The purpose of this qualitative study was to examine the perspectives of South Asian Indian immigrant women related to barriers to and motives for lifestyle PA within the PA Framework for South Asian Indian Immigrants. Forty women participated in focus groups that were conducted in English and Hindi. Focus group questions were open-ended and semistructured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Seven (32%, 7/22) studies addressed a lack of time as a barrier influencing attendance, participation and/or adherence in physical activity interventions [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. A lack of time was mainly due to household responsibilities and work obligations [ 25 , 26 , 27 , 28 , 29 , 30 ]. A study among Korean–Chinese immigrant women identified that individual occupational related time constraints were related to unstable employment, unfamiliar working conditions, unpredictable hours at work, lack of rest time, frequent changes of workplaces, difficulty in finding new work, long working hours, and/or increased job demands [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven (32%, 7/22) studies addressed a lack of time as a barrier influencing attendance, participation and/or adherence in physical activity interventions [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. A lack of time was mainly due to household responsibilities and work obligations [ 25 , 26 , 27 , 28 , 29 , 30 ]. A study among Korean–Chinese immigrant women identified that individual occupational related time constraints were related to unstable employment, unfamiliar working conditions, unpredictable hours at work, lack of rest time, frequent changes of workplaces, difficulty in finding new work, long working hours, and/or increased job demands [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four (18%, 4/22) studies addressed the individual health status as an influencing factor towards physical activity participation [ 28 , 30 , 31 , 32 ]. Optimal physiological and mental health conditions could facilitate participation in physical activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-efficacy, defined as the confidence to engage in physical activity, has been associated with greater participation in physical activity in general and among midlife women, including Latina women (Daniel et al, 2018; Janssen et al, 2014; Komar-Samardzija et al, 2012; Tovar et al, 2018). Conversely, the results of a comparative study showed that middle-aged women with T2D reported lower self-efficacy for physical activity than those without the condition (Vanden Bosch et al, 2015).…”
Section: Physical Activity In Middle-aged Women With T2dmentioning
confidence: 99%
“…Barriers are the negative consequences of determining whether the behavior is worth the benefits (Glanz et al, 2008). Study findings have indicated that several factors act as exercise barriers for middle-aged women with and without T2D: lack of time or motivation, disinterest, fatigue, feelings of embarrassment, life-stage commitments to family or others, lack of social support, injury, or fear of exercise-induced symptoms (Daniel et al, 2018; McGuire et al, 2014: Wilcox et al, 2000). Furthermore, the findings of one large study showed that urinary incontinence symptoms greatly decreased middle-aged women’s exercise participation (Nygaard et al, 2005).…”
Section: Physical Activity In Middle-aged Women With T2dmentioning
confidence: 99%